Measuring health care experiences that matter to Indigenous people in Australia with cancer: identifying critical gaps in existing tools - Monica Green; Joan Cunningham; Kate Anderson; Kalinda Griffiths; Gail Garvey (BMC, 2021)
Abstract Background Measurement of patients' healthcare experiences is increasingly used as an indicator of quality of care, but there are concerns that existing measures omit information that is meaningful to patients and that results may not be used systematically to inform service improvement. Further, current approaches may be inadequate for some population groups, such as Indigenous people in Australia, whose healthcare experience is impacted by the context of colonisation and discordance between Indigenous understandings of health and the Western biomedical health system. This study aimed to assess the extent to which existing patient experience measures used in Australia collect information about critical aspects of cancer care, as previously identified by Indigenous people affected by cancer and their health care providers. Methods A two-stage process was used to examine the adequacy of existing patient experience measures for Indigenous people in Australia: (1) relevant tools and measures were identified and assessed, and four measures selected as suitable comparators; (2) comparators were examined in detail and mapped against topics identified in earlier research as important to Indigenous people with cancer. Gaps in topic coverage in comparators were identified. Results No comparators completely captured the critical aspects of cancer care identified by Indigenous people affected by cancer and their health care providers. The number of topics 'partially' captured by the four comparators ranged from 4 to 7 out of 9. While most topics were partially covered, the lack of questions around culture and cultural safety was notable. Conclusions Existing tools are likely to miss key aspects of Indigenous peoples' experiences of cancer care in Australia. Failure to adequately assess care experiences related to cultural safety may compromise efforts to improve health outcomes. Addressing gaps requires development of experience measures that are strengths-based, reflect an Indigenous worldview and measure aspects of experience relevant to Indigenous people.